Reflecting Pictorial Language Design for Tactile Pictogram (Tactogram) - Fadhlillah, Fariz (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
This paper is intended to reflect on an appropriate pictorial language design for the tactogram. The research method used document study analysis based on the three previous studies. The data included the results of designing pictorial language using Tabrani's 'ancient visual language' theories. Tabrani revealed how to read stories in pictures through translating the drawn multiple images in a panel as motion descriptions of the object. The author assumed the descriptive image system as a suitable pictorial language concept in designing tactogram for the visually impaired as orientation and mobility system in train stations. In general, if the visually impaired still cannot understand the meaning of the tactogram symbols simultaneously with their sequential reading principle, then the pictorial language is not optimal yet. It indicates some errors in designing its system because it does not meet the visually impaired ability and habits to read tactile graphic-based information.